Social capital and physical activity: a literature review up to March 2024 - Zhendong Gao; Chen Soon Chee; Roxana Dev Omar Dev; Yutong Liu; Jianhong Gao; Rui Li; Fangyi Li; Xiaoxiao Liu; Tao Wang (Frontiers in Public Health)
BackgroundSocial capital, as a multidimensional social science concept, plays a crucial role in promoting physical activity. Despite numerous studies exploring the relationship between social capital and physical activity, there is still a lack of systematic understanding of how different dimensions of social capital influence physical activity levels. This study aims to systematically review the literature up to 2024 on the relationship between social capital and physical activity, uncover the role of social capital in promoting physical activity, and identify its multidimensional impacts.MethodsWe used a combination of search terms including “social capital” and “physical activity” to search the Web of Science, PubMed, Scopus, SportDiscus, and PsychINFO databases for English literature published up to March 1, 2024.ResultsWe identified 2,021 unique articles and reviewed 115 studies that met our inclusion criteria. These studies evaluated various dimensions of social capital, with key dimensions including social participation (34%), social networks (30%), social cohesion (30%), social trust (29%), overall social network (26%), social support (19%), safety (19%), norms of reciprocity (13%), social control (10%), satisfaction with the environment (8%), collective efficacy (4%), norms for physical activity (3%), and voting (1%). In studies exploring the relationship between social capital and physical activity, the majority of positive results in the hypothesized direction were observed in dimensions such as social cohesion, trust, participation, reciprocity, satisfaction with the environment, and overall social networks. In contrast, dimensions such as voting, collective efficacy, safety, control, and physical activity norms predominantly showed null or negative results. The results for social support were mixed, displaying positive, negative, and null outcomes, while findings for social networks were also predominantly mixed.ConclusionThis study reveals the significant role of social capital in promoting physical activity, particularly in the dimensions of social cohesion, social trust, social participation, norms of reciprocity, satisfaction with environment, and overall social network. When designing public health interventions in the future, it is crucial to tailor strategies to different populations and contexts to better leverage social capital in promoting physical activity.